Electrochemical Study of Pyridoxine (Vitamin B6) in Acetonitrile. Issue 3 (25th November 2014) - Lee, Jazreen H. Q.; Yue, Yanni; Ganguly, Rakesh; Webster, Richard D.
Abstract Cyclic voltammetry (CV) and controlled potential electrolysis (CPE) experiments revealed that at a Pt electrode, pyridoxine undergoes a one‐electron chemically irreversible oxidation at approximately 0.50 V versus Fc/Fc+, likely generating a dimeric product. Fouling of the electrode surface could be detected with repeated scans during CV and during preparative scale CPE oxidation experiments. These adsorption effects were overcome by performing bulk oxidation of pyridoxine with NOSbF6 as a chemical oxidant. At Pt electrodes, a cathodic wave associated with the reduction of pyridoxine was detected at approximately −1.60 V versus Fc/Fc+. The reduction process appeared to be chemically reversible on the shorter timeframe of CV, but not under the prolonged timescale of CPE. The reduction of pyridoxine involves a direct discharge of pyridoxine at the Pt surface, generating an oxide anion, which upon treatment with iodomethane yields N‐methylated pyridoxine rather than its O‐methylated analogue.